2016
DOI: 10.1088/1748-9326/11/6/064007
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen fertilization challenges the climate benefit of cellulosic biofuels

Abstract: Cellulosic biofuels are intended to improve future energy and climate security. Nitrogen (N) fertilizer is commonly recommended to stimulate yields but can increase losses of the greenhouse gas nitrous oxide (N 2 O) and other forms of reactive N, including nitrate. We measured soil N 2 O emissions and nitrate leaching along a switchgrass (Panicum virgatum) high resolution N-fertilizer gradient for three years post-establishment. Results revealed an exponential increase in annual N 2 O emissions that each year … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
70
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 80 publications
(76 citation statements)
references
References 40 publications
6
70
0
Order By: Relevance
“…When comparing AONRs among crops in 2013, a lack of overlap of the 95% CIs of the AONRs suggests that switchgrass required more N fertilizer to reach maximum biomass yield compared to TLI-C2 for grain yield at spring seeded locations. Increasing levels of N fertilization of switchgrass resulted in an exponential increase in N 2 O emissions, which can negate the climate change mitigation benefits of this bioenergy crop (Ruan et al, 2016). Additionally, reduced N fertilizer requirements for TLI-C2 offers economic incentives for adoption of this perennial crop.…”
Section: Agronomic Optimum Nitrogen Ratesmentioning
confidence: 99%
See 1 more Smart Citation
“…When comparing AONRs among crops in 2013, a lack of overlap of the 95% CIs of the AONRs suggests that switchgrass required more N fertilizer to reach maximum biomass yield compared to TLI-C2 for grain yield at spring seeded locations. Increasing levels of N fertilization of switchgrass resulted in an exponential increase in N 2 O emissions, which can negate the climate change mitigation benefits of this bioenergy crop (Ruan et al, 2016). Additionally, reduced N fertilizer requirements for TLI-C2 offers economic incentives for adoption of this perennial crop.…”
Section: Agronomic Optimum Nitrogen Ratesmentioning
confidence: 99%
“…Water quality could be improved as fertilized perennial crops leach less nitrate than annuals (McIsaac et al, 2010). Reducing N fertilization reduces greenhouse gas emissions related to N fertilizer volatilization (Ruan et al, 2016). Carbon sequestration occurs below perennials as root C is transferred via exudates and turnover to soil organic matter at depths where it is protected from decomposition (Tiemann and Grandy, 2015).…”
mentioning
confidence: 99%
“…Conversely, increased N 2 O emissions from N fertilizer were largely compensated for by increased yields in injected scenarios and, to a lesser extent, in broadcast ammonium nitrate scenarios. These results contrast with recent assertions that increased N application rate compromises the GHG mitigation benefits of cellulosic fuels (Ruan et al ., ). Although GHGs increased with N in broadcast urea scenarios, they were minimally affected by N application rate in broadcast ammonium nitrate scenarios and tended to decline slightly with increasing N application rate in injected scenarios, at least when expressed on an energy yield basis.…”
Section: Discussionmentioning
confidence: 97%
“…Methane fluxes reported in the literature from switchgrass production range from -3.8 to 2.4 g CH 4 -C ha -1 d -1 for fertilized monoculture switchgrass and −6.8 to -3.8 g CH 4 -C ha -1 d -1 for unfertilized switchgrass and are predominately sinks for CH 4 -C (Nikiema et al, 2011;Schmer et al, 2012;Wile et al, 2014;Raun et al, 2016). Total growing season soil CH 4 -C uptake was not significantly different among the PM, IC and SM treatments (Table 4).…”
Section: Ch 4 -C Flux Rates and Seasonal Emissionsmentioning
confidence: 99%
“…Schmer et al (2012) found N 2 O-N fluxes ranged from 0.24 to 8.6 g N 2 O-N ha -1 d -1 for fertilized switchgrass. Raun et al (2016) in a …”
mentioning
confidence: 99%